Respectus Philologicus, 2011 Nr. 19 (24) - Bankauskaitė, Gabija (Respectus Philologicus, 2011)
CONTENTS I. PROBLEMS AND SOLUTIONS Michał Mazurkiewicz (Poland). Sport versus Religion... 11 Natalia А. Kuzmina (Russia). Poetry Book as a Supertext... 19 Jonė Grigaliūnienė (Lithuania). Possessive Constructions as a Purely Linguistic Phenomenon?... 31 II. FACTS AND REFLECTIONS Aleksandras Krasnovas, Aldona Martinonytė (Lithuania). Symbolizing of Images in Juozas Aputis Stories...40 Jūratė Kumetaitienė (Lithuania). Tradition and Metamorphosis of Escapism (Running “from” or “into”) in the Modern and Postmodern Norwegian Literature...51 Natalia V. Kovtun (Russia). Trickster in the Vicinity of Traditional Modern Prose...65 Pavel S. Glushakov (Latvia). Semantic Processes in the Structure of Vasily Shukshin’s Poetics...81 Tatyana Kamarovskaya (Belarus). Adam and the War...93 Virginija Paplauskienė (Lithuania). Woman’s Language World in Liune Sutema’s Collection “Graffiti....99 Jolanta Chwastyk-Kowalczyk (Poland). The Models of e-Comunication in the Polish Society of Britain and Northern Ireland...111 Vilma Bijeikienė (Lithuania). How Equivocation Depends on the Way Questions are Asked: a Study in Lithuanian Political Discourse...123 Viktorija Makarova (Lithuania). The One Who Names the Things, Masters Them: Ruskij vs. Rosijanin, Ruskij vs. Rosijskij in the Discourse of Russian Presidents...136 Dorota Połowniak-Wawrzonek (Poland). Idioms from the Saga Film “Star Wars” in Contemporary Polish Language...144 Ilona Mickienė, Inesa Birbilaitė (Lithuania). Women’s Naming in Telsiai Parish in the First Dacades of the 18th Century...158 Liudmila Garbul (Lithuania). Reflection of Results of Interslavonic Language Contacts in the Russian Chancery Language of the First Half of the 17th Century (Synchronic and Diachronic Aspects). Part II...168 Vilhelmina Vitkauskienė (Lithuania). Francophonie in Lithuania... 179 Natalia V. Yudina (Russia). On the Role of the Russian Language in the Globalizing World of the XXI Century...189 Maria Lojko (Belarus). Teaching Legal English to English Second Language Students in the US Law Schools...200 III. OPINION Elena V. Savich (Belarus). On Generation of an Integrative Method of Discourse Analysis...212 Marek Weber (Poland). Lexical Analysis of Selected Lexemes Belonging to the Semantic Field ‘Computer Hardware’...220 IV. SCIENTISTS ABOUT SCIENTISTS Oleg Poljakov (Lithuania). On the Female Factor in Linguistics and Around It... 228 V. OUR TRANSLATIONS Bernard Sypniewski (USA). Snake in the Grass. Part II. Translated by Jurga Cibulskienė...239 VI. SCIENTIFIC LIFE CHRONICLE Conferences Tatiana Larina (Russia), Laura Alba-Juez (Spain). Report and reflections of the 2010 International Conference on Intercultural Pragmatics and Communication in Madrid...246 Books reviews Aleksandra M. Ponomariova (Russia). ЧЕРВИНСКИЙ, П. П., 2010. Номинативные аспекты и следствия политической коммуникации...252 Gabija Bankauskaitė-Sereikienė (Lithuania). PAPLAUSKIENĖ, V., 2009. Liūnė Sutema: gyvenimo ir kūrybos keliais...255 Yuri V. Shatin (Russia). Meaningful Curves. ГРИНБАУМ, О. Н., 2010. Роман А.С. Пушкина «Евгений Онегин»: ритмико-смысловой комментарий... 259 Journal of scientific life Daiva Aliūkaitė (Lithuania). The Idea of the Database of Printed Advertisements: the Project “Sociolinguistics of Advertisements”...263 Loreta Vaicekauskienė (Lithuania). The Project “Vilnius is Speaking: The Role of Vilnius Language in the Contemporary Lithuania, 2010”...265 Daiva Aliūkaitė (Lithuania). The Project “Lithuanian Language: Fractures of Ideals, Ideologies and Identities”: Language Ideals from the Point of View of Ordinary Speech Community Members...267 Announce...269 VII. REQUIREMENTS FOR PUBLICATION...270 VIII. OUR AUTHORS...278